(untitled) (Proceedings of International Educators Conference, 2023)
Emerging economies in the post-soviet area consider economic growth focused on innovation as an essential condition of ensuring sustainable growth in the 21st century. For this reason, governments of developing countries have adopted several state programs navigated to the stimulation of innovation in all sectors of economy. Likewise, the government of Uzbekistan has also chosen innovative development as country`s future economic and social wellbeing.